Anti-inflammatory and analgesic activity of Punarnavashtak Kwath, an ayurvedic formulation - Vineet Sharma (Wolters Kluwer Medknow Publications, 2017)
Context: Punarnavashtak Kwath (PNK) is a polyherbal formulation assumed to have the potential for curing all types of inflammation, hepatic disorders, and asthma. Aims: This study was conducted to establish the anti-inflammatory and analgesic activity of ethanol extract of PNK (EEPNK) in albino rats and mice. Subjects and Methods: The parts of the plant were air -dried in shade and pulverized coarsely and sieved by 20# sieve. Powdered material of plant was defatted with pet ether for 1 day followed by Soxhlet extraction with ethanol (95% v/v) for 7 days. The anti-inflammatory activity of the EEPNK was evaluated by egg albumin-induced paw edema and cotton pellet-induced granuloma tests to establish its effect on acute and chronic stage of inflammation models in albino rats. Whereas analgesic effects of EEPNK were performed in mice of either sex by acetic acid-induced writhing and hot plate methods. Statistics was expressed as a mean ± standard error of mean and statistical analysis was carried out by one-way ANOVA with Tukey's test. Results: The percent inhibition in rat paw volume was dose dependent (79.14%, 68.51%, and 61.70% at doses of 400, 200, and 100 mg/kg, p.o., respectively) at 240 min readings. Cotton pellet granuloma in rats (chronic study) model EEPNK (400, 200 and 100 mg/kg, p.o.) extensively decreased the granuloma weight as compared to the negative control animals. Pretreatment with EEPNK was (400, 200, and 100 mg/kg p.o.) extensively (P < 0.001) inhibited of writhings in mice, and also significantly (P < 0.001) increased pain latency in hot plate test. Conclusions: Distinguish with the standard drug (indomethacin), the elevated dose of EEPNK (400 mg/kg b.w.) has a comparable effect on the anti-inflammatory and analgesic activities.